Solvent‐Free Photobiocatalytic Hydroxylation of Cyclohexane. Issue 16 (12th June 2020) - Hobisch, Markus; van Schie, Morten Martinus Cornelis Harald; Kim, Jinhyun; Røjkjær Andersen, Kasper; Alcalde, Miguel; Kourist, Robert; Park, Chan Beum; Hollmann, Frank; Kara, Selin
Abstract: The use of neat reaction media, that is the avoidance of additional solvents, is the simplest and the most efficient approach to follow in biocatalysis. Here, we show that unspecific peroxygenase from Agrocybe aegerita ( Aae UPO) can hydroxylate the neat model substrate cyclohexane. H2 O2 was photocatalytically generated in situ by nitrogen‐doped carbon nanodots (N−CNDs) and UV LED illumination. Aae UPO entrapment in alginate beads increased enzyme stability and facilitated the reaction in neat cyclohexane. N−CNDs absorption in beads containing Aae UPO created a 2‐in‐1 heterogeneous photobiocatalyst that was active for up to seven days under reaction conditions and produced cyclohexanol, 2.5 mM. To increase productivity, the bead size and the photocatalyst‐to‐enzyme ratio have been identified as promising targets for optimisation. Abstract : Photobiocatalysis : In this communication we demonstrate the potential of peroxygenase for light driven hydroxylation of neat cyclohexane. The new generation easy‐to‐prepare carbon nanodots and gel‐entrapped peroxygenase were applied as 2‐in‐1 photobiocatalyst in a neat substrate system.